Enhancement of Flexural Behavior Using Minimal Reinforced Concrete and Steel Slag as Fine Aggregate Replacement - Sofianto, Mochamad Firmansyah; Wulandari, Meity; Nugroho, Yanuar Bayu; Heryanto, Muhammad Titho (Kadiri University, 2025)
The ductility capacity of structural elements is influenced not only by the reinforcement steel but also by the quality of the concrete material. Recent mix designs increasingly consider the incorporation of industrial by-products such as steel slag. Therefore, steel slag waste can be utilized as an alternative material in the reinforced concrete, especially for simple beam elements. This study aims to determine the effectiveness of steel slag as a fine aggregate replacement for beams as simple structural elements. The replacement ratios of steel slag were 1%, 3%, 5%, and 7% by weight of fine aggregates. The specimens included cylindrical samples for compressive strength testing and rectangular beam with 100 cm in span, for flexural testing. Beam elements conducted with two points of loading and recorded the deflection in middle and draw the crack pattern on beam element. The results revealed that the highest compressive strength, 33.24 MPa, was achieved with a 7% steel slag substitution. A higher proportion of steel slag affected the deflection behavior and internal force capacity. Initial cracking occurred at an external load of approximately 800 kg, while reinforcement yielding was observed at around 2500 kg, leading to ultimate failure. The maximum deflection of 9.25 mm was recorded for the 7% mixture, which also demonstrated the highest moment capacity. Overall, the findings confirm that partial substitution of sand with steel slag significantly enhances the flexural performance of concrete beams, thus providing a sustainable material solution.